2019
DOI: 10.3390/antiox8080258
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and Antioxidant Properties of a New Lipophilic Derivative of Edaravone

Abstract: As part of a program aimed to obtain antioxidants able to interact with cell membrane, edaravone (EdV, 3-methyl-1-phenyl-2-pyrazolin-5-one), a well-known free radical scavenger, has been modified by alkylation at its allylic position (4) with a C-18 hydrocarbon chain, and the increased lipophilicity has been determined towards the interaction with liposomes. The obtained derivative has been studied by means of density functional theory (DFT) methods in order to characterize its lowest energy conformers and pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 45 publications
1
26
0
Order By: Relevance
“…As previously reported, even though the EGCG structure enables it to interact with the the polar heads of phospholipids present in the bilayer [15,51], only part of EGCG molecules is efficiently bound to the lipid mambrane. Part of EGCG molecules lies in the water phase, thus able to react with the radicals generated from AAPH decomposition, preventing them to interact with membrane lipids.…”
Section: Structural Insight Of C18-egcg Inside Lipid Bilayer: In Silimentioning
confidence: 60%
See 1 more Smart Citation
“…As previously reported, even though the EGCG structure enables it to interact with the the polar heads of phospholipids present in the bilayer [15,51], only part of EGCG molecules is efficiently bound to the lipid mambrane. Part of EGCG molecules lies in the water phase, thus able to react with the radicals generated from AAPH decomposition, preventing them to interact with membrane lipids.…”
Section: Structural Insight Of C18-egcg Inside Lipid Bilayer: In Silimentioning
confidence: 60%
“…The stabilization of EGCG can be obtained by different approaches including the employment of reducing agents, structural modification and/or drug delivery systems [12][13][14]. Among these, the application of derivatization strategies designed to increase the molecule hydrophobicity and the interaction with cellular membrane [15][16][17][18][19][20] is considered as a feasible approach to improve the activity of bioactive molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Edaravone (ED) is a free radical scavenger that protects the cerebral functions, and is a first-line drug in clinical treatment of cerebral infarction (Parikh et al, 2017; Tokumaru et al, 2018). ED scavenges free radicals, inhibits lipid peroxidation and alleviates ischemia-reperfusion injury (Fujisawa & Yamamoto, 2016; Uchiyama et al, 2015) , moreover, as it has antioxidant properties, ED is the first free radical scavenger clinically proved to be a neuroprotective agent in Japan since 2001 (Minnelli et al, 2019) , and it plays an important role in alleviating oxidative stress in some diseases (Kikuchi et al, 2012) . Takeo Koizumi et al (Koizumi et al, 2006) showed that ED could reduce the free radical precursors and their metabolites in extensively burned rats.…”
Section: Introductionmentioning
confidence: 99%
“…Edaravone combined with the lipid system enhanced the antioxidant function of edaravone. 35 Caspase-3, as a member of the caspase family, is S-nitrosylated on its catalytic site Cys163, which inhibits its protease activity. 18 , 36 The levels of cleaved caspase 3 were significantly increased in the propofol group, leading to cell death.…”
Section: Discussionmentioning
confidence: 99%